Efficacy of the Uses of Hypermedia: Photography and Auto Photography in English Language Teaching on the Performance of English Language Writing Skill - Mohideen Bawa Nowzath (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
The application of hypermedia-based photography and auto photography learning; basically refers to facilitate the learning process through the control of visuals, images: practice of taking and processing photographs, animation, sound and other multimedia information with the assistance of hypertext, aligned to selected learning strategies shows a major role in the performance of the students. This research was conducted to find the relationship between the hypermedia-based learning of photography and auto photography under selected categories in the HNDE syllabus with proper learning strategies: tasks and schedules in word platform with photography and auto photography method and the performance in the English language writing skill in HNDE course of ATI – Sammanthurai of SLIATE as there were no any previous research studies done in this area of the academic field. Ninety students from HNDE – class – first year - A were taken as experimental group and ninety students from class - first year - B were taken as controlled group. A pre-test was conducted for both the groups to find out the previous knowledge of the students in the groups in order to compare them and the mean differences were found to be negligible for both the groups from the pre-test. Later, the experimental group was used in the classroom to pursue hypermedia-based photography and auto photography learning based on selected learning strategies for six months with sixty hours learning while the controlled group was generally taught without the use of hypermedia-based photography and auto photography learning. After six months a post-test was conducted for both the groups. When the post-test was conducted the mean (-0.091) was slightly improved for the group - B than the pre-test, and the mean (-2.871) was considerably improved for the group - A in the post-test. Thus, it is found that there is a positive relationship between the hyper-media based photography and auto photography learning using selected learning strategies and the performance in the English language writing skill. The research findings imply that hyper-media based photography and auto photography learning improves English language writing skill of the learners.